2020
DOI: 10.1177/1569186120921472
|View full text |Cite
|
Sign up to set email alerts
|

Prism adaptation treatment for spatial neglect post brain tumour removal: A case report

Abstract: Purpose/aim: Spatial neglect is caused by damage to neural networks critical for spatial attention. Spatial neglect without proper treatment impedes rehabilitation outcomes. Prism adaptation treatment, a visuomotor protocol, has been used with stroke survivors with spatial neglect to improve function. This case report explored the feasibility and potential effects of prism adaptation treatment in an individual with spatial neglect after glioblastoma removal. Methods Feasibility was designed and tested to inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Modified from a five-object figure copying test [ 6 ], the Scene Copying Test is a figure copying task consisting of two plants, a house, and two trees arranged in that order left-to-right, printed on the upper half of a page [ 56 ]. The task is to copy the entire “scene” to the lower half of the page.…”
Section: Methodsmentioning
confidence: 99%
“…Modified from a five-object figure copying test [ 6 ], the Scene Copying Test is a figure copying task consisting of two plants, a house, and two trees arranged in that order left-to-right, printed on the upper half of a page [ 56 ]. The task is to copy the entire “scene” to the lower half of the page.…”
Section: Methodsmentioning
confidence: 99%
“…The prism goggles were used only during PAT (for detailed procedures, see the KF-PAT manual 40 or previous reports). 2 , 42 , 43 PAT was delivered once a day during an OT session, mostly at the beginning of the session. Some sites followed the recommendation of delivering PAT over 10 consecutive days or weekdays (skipping weekends), and others completed as many PAT sessions as possible, depending on individual patients’ condition and length of stay (LOS).…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of spatial neglect (SN) is approximately 20%-40% among survivors of stroke in acute and postacute inpatient settings and it is more common after right brain damage than left brain damage. 1 SN can also occur in individuals with other types of brain injury 2 , 3 because the disorder results from damage to the neural networks critical to spatial processing and attention control. 4 , 5 Affected individuals typically demonstrate ipsilesional bias and hence pay no or insufficient attention to the contralesional side of space.…”
mentioning
confidence: 99%
“…Prism adaptation treatment (PAT; for detailed treatment procedures and mechanisms, see recent reviews) 12 -15 is promising in reducing SN symptoms and improving functional outcomes. 16,17 We conducted a retrospective, matched control study (N = 312) 18 that demonstrated the effectiveness of PAT when embedded in occupational therapy practice on inpatient rehabilitation outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In the overarching implementation project, 29 therapists were encouraged to assess all neurological patients under their care, with the understanding that SN can occur after different types of brain injury, using the Catherine Bergego Scale (CBS) via the Kessler Foundation Neglect Assessment Process (KF-NAP®). 30,31 Therapists were encouraged to deliver PAT following the Kessler Foundation Prism Adaptation Treatment (KF-PAT®) protocol 13,22 when SN was detected. The primary goal was to train all participating therapists in integrating both KF-NAP and KF-PAT in their practice.…”
Section: Introductionmentioning
confidence: 99%